Efficacy of therapeutic intervention with NanoBEO to manage agitation and pain in patients suffering from severe dementia: a pilot clinical trial - Scuteri, Damiana; Pagliaro, Martina; Mantia, Isabel; Contrada, Marianna; Pignolo, Loris; Tonin, Paolo; Nicotera, Pierluigi; Bagetta, Giacinto; Corasaniti, Maria Tiziana; , the Pilot BRAINAID Trial investigators (Frontiers in Pharmacology, 2024)
Background An estimated 57.4 million people live with dementia worldwide, with the social burden of the disease steadily growing. Despite the approval of lecanemab and ongoing trials, there is still a lack of effective and safe treatments for behavioral and psychological symptoms of dementia (BPSD), which affect 99% of patients. Agitation is one of the most disabling BPSD, with a cross-sectional prevalence of ≥50% in nursing homes, and refers to help-seeking behavior in response to various sources of discomfort, among which pain is a crucial component. Methods This pilot phase of the BRAINAID (NCT04321889) trial aimed to assess the effectiveness of the patented nanotechnological device NanoBEO in older (≥65 years) people with severe dementia. This randomized placebo-controlled trial, with quadruple masking that involved all operators and participants, followed the SPIRIT and CONSORT statements. A total of 29 patients completed the trial. The patients were randomly allocated in a 1:1 ratio to the NanoBEO or placebo group, and the corresponding product was applied on both arms once daily for 4 weeks, with a 4-week follow-up period. The primary endpoint was efficacy against agitation. The secondary endpoints were efficacy against agitation at follow-up and efficacy against pain. Any adverse events were reported, and biochemical analyses were performed. Results The NanoBEO intervention reduced the frequency (28%) and level of disruptiveness of agitated behaviors. The effect on frequency was statistically significant after 2 weeks of treatment. The efficacy of NanoBEO on agitated behaviors lasted for the entire 4-week treatment period. No additional psychotropic drugs were prescribed throughout the study duration. The results after 1 week of treatment demonstrated that NanoBEO had statistically significant analgesic efficacy (45.46% improvement in pain intensity). The treatment was well tolerated. Discussion This trial investigated the efficacy of NanoBEO therapy in managing agitation and pain in dementia. No need for rescue medications was recorded, strengthening the efficacy of NanoBEO in prolonged therapy for advanced-stage dementia and the usefulness of the intervention in the deprescription of potentially harmful drugs. This study provided a robust rationale for the application of NanoBEO in a subsequent large-scale pivotal trial to allow clinical translation of the product. Clinical Trial Registration:ClinicalTrials.gov, identifier NCT04321889.